(untitled) (Eurasian Journal of Learning and Academic Teaching, 2022)
This article is about ways of teaching students to self-study, creative thinking through organizing practical lesson with innovative technologies at higher educational organization. This article describes the problem of increasing the self activite of the assimilation of knowledge independent thinking by organizing self-education in higher educational institutions.